Stress and fitness in parthenogens: is dormancy a key feature for bdelloid rotifers? - Ricci, Claudia (BioMed Central|1, 2007)
BACKGROUND: Bdelloid rotifers are the most common and abundant group of animals that reproduce by ameiotic parthenogenesis, only. They are common in temporally ephemeral habitats, and it is unclear if they dwell in unstable habitats because are excluded from better conditions by stronger competitors, or because they need unstable conditions for their success. We tested the hypothesis that bdelloids 'require' stressful conditions for their persistence by comparing fitness-related traits of stressed (desiccated, D) and unstressed (hydrated, H) lines of two species, Adineta ricciae and Macrotrachela quadricornifera. RESULTS: For both bdelloid species, fecundity was significantly lower in H than in parallel D line. Fitness components decreased with time progressively in the H line but not in the D line. Recovery rates of D lines were recorded after every desiccation and did not reveal any trend in time, suggesting that no selection was operating. CONCLUSION: Stress in the form of reiterated desiccations seemed to help both bdelloid species to keep fitness stable; in contrast under stable conditions, like permanent hydration, these bdelloid species had poorer performances. Bdelloids, although aquatic animals, are not only efficient in tolerating desiccation, but seem somehow dependent on anhydrobiosis, a circumstance that might represent a key event in their life cycle. If this is true, life in unpredictable habitats should not be seen as the result of competitive exclusion from 'easier' habitats, but a requirement for long-term survival of these parthenogenetic animals.